Erianthus Plant: A Rich Silica Source for Extraction of Amorphous Silica - het Mya Mya Sein; El Mon Aung (ASEAN Journal of Chemical Engineering, 2021)
In this paper, Erianthus plant, a grass type of lignocellulosic biomass, is presented as an alternative source for the production of amorphous silica. Thermal treatment (combustion) of Erianthus plant under a controlled temperature of 600–900°C produces Erianthus Ash (EA). Then, silica powder was extracted from EA by the chemical extraction method. In this work, the effect of treatment temperature on the preparation of EA and extracted silica is studied. The EA samples and extracted silica are noted as EA600 – EA900 and Si600 – Si900 respectively with respect to the treatment temperature. To evaluate the effect of the concentration of NaOH solution on the purity of silica, NaOH solution (2–3 N) is verified in this work. The results revealed that the pure amorphous silica can be extracted using a 2.5 N NaOH solution from EA800. The percentage of amorphous silica with a purity of about 99% was confirmed by X-Ray Fluorescence (XRF).